2020
DOI: 10.1007/s00068-020-01440-y
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular osteotomy of malunited tibial plateau fractures: an analysis of clinical results with a mean follow-up after 4 years

Abstract: Purpose Malunions are a common complication after tibial plateau fractures (TPF), leading to stiffness, pseudo-instability and posttraumatic osteoarthritis. The purpose of this study was to analyse the clinical outcome after intraarticular osteotomy of malunited TPF and to perform a failure analysis. Methods Between 2013 and 2018, 23 patients (11 males, 12 females; 43.8 ± 12.8 years) with intraarticular osteotomy after malunited TPF were included in the retrospective study. Clinical examination and postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…In combined malunions, several techniques can be combined, and treatment should be performed in two stages separated by 3-6 months to ensure consolidation (91). Table 4 shows a summary of the results from the literature on the treatment of malunions (94,96,97,98,99,100).…”
Section: Treatmentmentioning
confidence: 99%
“…In combined malunions, several techniques can be combined, and treatment should be performed in two stages separated by 3-6 months to ensure consolidation (91). Table 4 shows a summary of the results from the literature on the treatment of malunions (94,96,97,98,99,100).…”
Section: Treatmentmentioning
confidence: 99%
“…It is commonly known that persistent post-operative knee stiffness results in impaired patient-related outcome [4,16,17]. Previous studies demonstrated that impaired postoperative functional scores correlated with a post-operative extension and flexion deficit in primary and revision osteosynthesis of tibial head fractures [3,5]. Also, Mayr et al showed that patients with post-operative motion loss suffered from long-term complications: thus, nearly 80% of their patients with arthrofibrosis showed signs of osteoarthritis in the femoro-tibial joint five years after arthroscopic arthrolysis [14].…”
Section: Discussionmentioning
confidence: 99%
“…When the ACL reconstruction (ACLR) is combined with an open reconstruction of the medial collateral ligament (MCL), the incidence of post-operative motion loss is even higher with rates up to 13% [1,2]. Following the surgical treatment of tibial plateau fractures (TPF), the rate of a loss of motion was shown to be 14%, and after revision procedures, it may even raise up to 50% of the cases [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, osteotomy might be a good but technically demanding treatment option. In the article "Intraarticular osteotomy of malunited tibial plateau fractures: an analysis of clinical results with a mean follow-up after 4 years ", the authors reported on good outcomes with proper realignment of the lower limb axis as well as intra-articular step-offs 4 years after an osteotomy due to malreduction or non-union [1]. Nevertheless, these procedures should be limited to experts and centers with a high case load.…”
mentioning
confidence: 99%
“…This issue thoroughly presents articles around the tibial plateau [1,6,10,11,[15][16][17]. One important aspect needs, however, further investigations in the future: many surgeons are still focusing mainly on the osseous reconstruction, while soft tissues might be underestimated or even neglected.…”
mentioning
confidence: 99%